2012
DOI: 10.5038/1936-4660.5.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Number Sense: The Underpinning Understanding for Early Quantitative Literacy

Abstract: The fundamental meaning of Quantitative Literacy (QL) as the application of quantitative knowledge or reasoning in new/unfamiliar contexts is problematic because how we acquire knowledge, and transfer it to new situations, is not straightforward. This article argues that in the early development of QL, there is a specific corpus of numerical knowledge which learners need to integrate into their thinking, and to which teachers should attend. The paper is a rebuttal to historically prevalent (and simplistic) vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The evidence contributed by this study bolsters that QL/QR also plays and important role. Students need the ability to do simple calculations (add, subtract, multiply, and divide) with minimal mental effort by having these basics committed to long-term memory for easy retrieval (i.e., the preferred outcome and desirable condition needed for success). , …”
Section: Literature Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence contributed by this study bolsters that QL/QR also plays and important role. Students need the ability to do simple calculations (add, subtract, multiply, and divide) with minimal mental effort by having these basics committed to long-term memory for easy retrieval (i.e., the preferred outcome and desirable condition needed for success). , …”
Section: Literature Backgroundmentioning
confidence: 99%
“…Successful implementation of numeracy skills requires habits of mind that include prior knowledge and automaticity of arithmetic. , As Maclellan points out, no argument can be made that using QL/QR is critical in society but the inability to apply QL/QR skills in new situations (such as a chemistry course) is extremely problematic . A quantitatively literate student has the ability to reason and synthesize information, interpret problems, and ask thought-out questions to make informed decisions on how to solve the problem(s) at hand .…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Pre-primary mathematics education was found to be a helpful content since it is through mathematics that children construct a solid base for school achievement. Numbers and operations come first when delivering the preprimary mathematics content because they prepare a basis for children's prospect of educational achievements in mathematics (Yilmaz, 2017) and it was highlighted that teachers' understanding of the concepts of numbers and operations helps them create the foundation of young children's math understanding (Maclellan, 2012).…”
Section: Teachers With Mathematics Content In Preprimary Schoolmentioning
confidence: 99%
“…Further, learning to count enables children to develop the language of numbers and leads the children to take a grasp on the meanings of songs they sang before starting school, makes the children know more numbers through counting, and it helps the children know how they can solve the different mathematical equations. However, it was found that teachers still have gaps in teaching numbers and operations (Maclellan, 2012). Thus, teachers need to possess a special kind of knowledge relevant to the level of pre-primary children and also to the mathematics content areas discussed here especially the area of numbers and operations as it helps children to easily understand other mathematics content areas.…”
Section: Teachers With Mathematics Content In Preprimary Schoolmentioning
confidence: 99%
“…There has been a growing body of research evidence, over the last 30 years, in the area of mathematics teaching connecting effective learning with teachers' knowledge of how children are conceptualising (and misconceptualising) mathematical principles (Ball, Thames and Phelps, 2008;Carpenter, Fennema and Peterson et al, 1988;Greer and Meyen, 2009;Jacobs, Lamb and Philipp, 2010;Maclellan, 2012;Peterson, Fennema and Carpenter et al, 1989;Ryan and Williams, 2007). The recognition of this kind of pedagogical knowledge as relevant for all children connects with inclusive arguments which promote the extension of what is commonly available for all as a means of accommodating difference (Florian and Black-Hawkins, 2011;Hart, Drummond and McIntyre, 2007;Norwich and Nash, 2011;Ylonen and Norwich, 2012).…”
Section: Introductionmentioning
confidence: 99%